Reproducible research in pattern recognition : first International Workshop, RRPR 2016, Cancún, Mexico, December 4, 2016, Revised selected papers /: first International Workshop, RRPR 2016, Cancún, Mexico, December 4, 2016, Revised selected papers. (2017) - Unknown
No abstract available